Taxonomy of Three Oxytrichids (Protozoa, Ciliophora, Hypotrichia), With Establishment of the New Species Rubrioxytricha guangzhouensis spec. nov. - Luo, Xiaotian; Huang, Jie; Bourland, William A.; El-Serehy, Hamed A.; Al-Farraj, Saleh A.; Chen, Xumiao; Song, Weibo (Frontiers in Marine Science, 2021)
Two oxytrichid ciliates collected from China, Oxytricha lithofera Foissner, 2016 and Rubrioxytricha haematoplasma (Blatterer & Foissner, 1990) Berger, 1999, were investigated based on living observations, protargol preparations, and molecular analyses. The Chinese population of O. lithofera shares highly distinctive features with the type population, e.g., lithosomes, abutting macronuclear nodules, straight undulating membranes, and long dorsal bristles. The morphology and morphogenesis of our new isolate of R. haematoplasma corresponds well with the type population. The 18S rRNA gene sequences of both organisms were obtained and the molecular phylogeny of these two genera was analyzed. In addition, we found that the Guangzhou population of R. haematoplasma sensu Chen et al. (2015) can be distinguished from the type population and our new isolate by having two types of cortical granules, that is, type-I, reddish-brown, type-II, colorless (vs. only one type, lemon yellowish to greenish), as well as the reddish-brown cytoplasm (vs. slightly orange) and the marine or brackish water habitat (vs. freshwater). In addition, 20 bp divergence in their 18S rRNA gene sequences indicate that they are not conspecific. Thus, a new species, Rubrioxytricha guangzhouensis, is established for the R. haematoplasma sensu Chen et al. (2015) in this work.